Impact of genetic test interpretation on a VPS13B missense variant in Cohen syndrome - Gudrun Schottmann; Carmen Martínez Almudéver; Julia C. M. Knop; Eun Kyung Suk; Zianka Meyer; Jürgen Kohlhase; Nastassja Himmelreich; Nastassja Himmelreich; Jirko Kühnisch; Jirko Kühnisch; Claus-Eric Ott; Wenke Seifert (Frontiers in Neuroscience)
IntroductionCohen syndrome (CS) is an early-onset pediatric neurodevelopmental disorder characterized by postnatal microcephaly and intellectual disability. An accurate diagnosis for individuals with CS is crucial, particularly for their caretakers and future prospects. CS is predominantly caused by rare homozygous or compound heterozygous pathogenic variants in the vacuolar protein sorting-associated 13B (VPS13B) gene, which disrupt protein translation and lead to a loss of function (LoF) of the encoded VPS13B protein.MethodsThe widespread incorporation of next-generation sequencing approaches in genetic diagnostics increases the number of individuals carrying VPS13B mutant alleles. At the same time, it increases the detection of variants of unknown clinical significance, necessitating further functional pathogenicity validation.ResultsIn this study, we present a family with two CS patients. Within this family, four rare VPS13B variants were detected: c.710G > C, p.Arg237Pro; c.6804delT, p.Phe2268Leufs*24; c.7304C > T, p.Ala2435Val; and c.10302T > A, p.Tyr3434*. These variants challenge the interpretation of their disease-causing role. Specifically, the variants c.6804delT, p.Phe2268Leufs*24 and c.710G > C, p.Arg237Pro were detected in trans configuration and are considered to be causing CS genetically. The functional characterization of the missense variant c.710G > C, p.Arg237Pro shows diminished localization at the Golgi complex, highlighting its clinical relevance and supporting its classification by the American College of Medical Genetics and Genomics (ACMG) as likely pathogenic, class 4.DiscussionOverall, we emphasize the need for combining genetic and functional testing of VPS13B missense variants to ensure accurate molecular diagnosis and personalized medical care for CS patients.